Electrophysiological analysis of cardiac K ATP channel - Huo, Jianyi; Yang, Hua-Qian (Biophysics reports, 2025)
ATP-sensitive potassium (K ) channels are integral components in excitable cells, particularly in cardiomyocytes, serving as critical regulators of cellular metabolism and electrical excitability. In instances of prolonged oxygen deprivation or heightened metabolic requirements, the opening of K channels enables potassium efflux by virtue of a diminished ATP/ADP ratio. This process aids in maintaining membrane potential stability, thereby mitigating excessive excitability and cellular contraction, ultimately contributing significantly to cardiac protection. The accurate isolation of intact single cardiomyocytes and the electrophysiological evaluation of K channels are pivotal processes in research on K channels in cardiomyocytes . Here, we present a comprehensive protocol not only for the efficient isolation of viable cardiomyocytes from the adult mouse through the Langendorff perfusion method, but also for the recording of K channel currents in single cardiomyocytes employing patch clamp technique.